Operational challenges and lessons learned from conducting febrile surveillance in a long-term randomized dengue vaccine trial in Latin America and Asia-Pacific - Harald Pfaar; Eduardo López-Medina; Ian Escudero; Yanee Hutagalung; Nicholas Roubinis; Seloni Thakrar; Charissa Fay Corazon Borja-Tabora; Vianney Tricou; Suely Tuboi (Travel Medicine and Infectious Disease)
Background: In trials, dengue vaccine efficacy evaluation relies on participants presenting with febrile illness/clinically suspected dengue contacting the study site for sample collection and clinical assessment within a short timeframe. Here, we present key considerations to maintain high compliance with the febrile surveillance procedures in a trial that assessed TAK-003 efficacy. Methods: DEN-301 (NCT02747927) is a randomized phase 3 trial in children/adolescents from eight dengue-endemic countries in Latin America (LATAM) and Asia-Pacific (APAC). Febrile surveillance consisted of weekly contact with the participant to identify cases of fever (≥38 °C; two of three consecutive days). Blood samples were collected for molecular testing, preferably ≤5 days of fever onset, together with thorough clinical assessment by the investigators. The data are presented descriptively. Results: Of the 20,071 (LATAM, 11,080; APAC, 8991) participants who received TAK-003/placebo, 18,260 (91.0 %) completed 4.5 years of follow-up. The overall incidence of febrile illness was 30 (LATAM, 26.0; APAC, 35.1) cases per 100 person-years. The rate samples collected during the acute phase was 98.1 %. The overall rate of samples collected after 5 days of fever onset (missed/out-of-window) was 6 % (LATAM, 10 %; APAC, 2 %). A trend toward reduced missed/out-of-window samples was observed after implementing measures, such as transportation, engagement, and healthcare aid tailored per study site in 2017, which appeared to increase during the COVID-19 pandemic. Conclusion: The design of the febrile surveillance protocol ensured high compliance in the trial. Maintaining engagement and access to healthcare beyond the protocol was important in improving febrile case evaluation ≤5 days of fever onset.